Religiosity in Central and Eastern Europe. Facts and Interpretations - Tomka, Miklós (Religion and society in Central and Eastern Europe, 2010)
It is commonly acknowledged that the current situation in Central and Eastern Europe reflects twogreat social cataclysms. The end of the second World War and the Communist takeover meant thebeginning of an artificial social experiment’ that generated significant changes. This experiment failed.The second cataclysmic event, which occurred in 1989, again precipitated radical changes in the socioeconomicrelationships. In fact, three different models followed each other not only in the political, butalso in the social order. In the meantime, the roles and the relational positions of the elements in thesocial system as well as the individuals’ possibilities have changed. These changes dramatically affectedreligion. Before 1945, religion had been one of the main pillars of the societal order and the state, butunder the Communist era it was persecuted and pushed to the private sphere. Since 1989, it hasresumed to be a public actor whose precise role, however, has not been finalized yet (Bremer 2008,Pollack, Borowik, Jagodzinski 1998, Spieker 2003). The fact that the second half of the 20th century isnot only a sequence of different political systems but also a process of modernization makes thesituation even more complicated. Due to the dictatorial nature of this process, we may call it a"Communist type of modernization".